2004
DOI: 10.1088/0965-0393/12/4/s10
|View full text |Cite
|
Sign up to set email alerts
|

First principles force field for metallic tantalum

Abstract: We propose a general strategy to develop accurate Force Fields (FF) for metallic systems derived from ab initio quantum mechanical (QM) calculations; we illustrate this approach for tantalum. As input data to the FF we use the linearized augmented plane wave method (LAPW) with the generalized gradient approximation (GGA) to calculate: (i) the zero temperature equation of state (EOS) of Ta for bcc, fcc, and hcp crystal structures for pressures up to ∼ 500 GPa. (ii) Elastic constants. (iii) We use a mixed-basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 61 publications
(122 reference statements)
6
24
0
Order By: Relevance
“…Collectively, the Ta melt curves presented in Ta: Large-cell two-phase and slope, T m and dT m / dP , at P = 0 are 3222 K and 51 K/GPa, respectively -in good agreement with experimental measurements of 3270 K [7,11] and ~ 59 K/GPa [11] and also in accord with other recent theoretical results [18][19][20]. The calculated T m at the observed shock melt pressure of 295 GPa [15] is 10000 K and close to the value recently measured by pyrometry of ~ 9700 K. As a further point of interest in Fig.…”
Section: High-temperature Anharmonicitysupporting
confidence: 90%
“…Collectively, the Ta melt curves presented in Ta: Large-cell two-phase and slope, T m and dT m / dP , at P = 0 are 3222 K and 51 K/GPa, respectively -in good agreement with experimental measurements of 3270 K [7,11] and ~ 59 K/GPa [11] and also in accord with other recent theoretical results [18][19][20]. The calculated T m at the observed shock melt pressure of 295 GPa [15] is 10000 K and close to the value recently measured by pyrometry of ~ 9700 K. As a further point of interest in Fig.…”
Section: High-temperature Anharmonicitysupporting
confidence: 90%
“…6b, the present full-theory result is in good accord with the measured data of Touloukian et al [47] up to about 400 K and still in reasonable agreement to 1000 K, again capturing the observed behavior in both the quantum and classical temperature regimes. Above 1000 K, however, the data has large error bars and begins to diverge from the theory, and only provisional values of thermal expansion were measured above 2000 K. In a similar manner, the steep rise in the Touloukian et al data above 2000 K was found to move rapidly above the corresponding DFT-based result of Cohen and Gülseren [42] as well as the EAM-MD calculations of β in Ta by Strachan et al [48].…”
Section: B Qhld MD and Vpt Implementation Of Mgpt Potentialsmentioning
confidence: 72%
“…Two EAM potentials are of particular interest: one by R. Ravelo et al (this proceedings) simply denoted as EAM, and the other by Strachan et al denoted as qEAM [1]. We show that both potentials reproduce the experimental Hugoniots, and reveal the anisotropic deformation and damage processes in single crystal Ta.…”
Section: Introductionmentioning
confidence: 68%
“…The Ta EAM potential adopts the standard EAM form (R. Ravelo et al, this proceedings), while for the qEAM potential, the electron density depends on the local volume or mass density [1]. Such volume dependence may be a concern for the later stage of spallation (large voids), so we choose not to perform direct spall simulations with qEAM.…”
Section: Methodsmentioning
confidence: 99%